The Potential of Peroxidases Extracted from the Spent Mushroom (Flammulina velutipes) Substrate Significantly Degrade Mycotoxin Deoxynivalenol - Tso, Ko-Hua; Lumsangkul, Chompunut; Ju, Jyh-Cherng; Fan, Yang-Kwang; Chiang, Hsin-I (Toxins, 2021)
Little is known about the degradability of mycotoxin deoxynivalenol (DON) by the spent mushroom substrate (SMS)-derived manganese peroxidase (MnP) and lignin peroxidase (LiP) and its potential. The present study investigated the growth inhibition of Fusarium graminearum KR1 and the degradation of DON by MnP and LiP extracted from SMS. The results from the 7-day treatment period showed that mycelium inhibition of F. graminearum KR1 by MnP and LiP were 23.7% and 74.7%, respectively. Deoxynivalenol production in the mycelium of F. graminearum KR1 was undetectable after treatment with 50 U/mL of MnP or LiP for 7 days. N-acetyl-D-glucosamine (GlcNAc) content and chitinase activity both increased in the hyphae of F. graminearum KR1 after treatment with MnP and LiP for 1, 3, and 6 h, respectively. At 12 h, only the LiP-treated group had higher chitinase activity and GlcNAc content than those of the control group (p < 0.05). However, more than 60% of DON degradabilities (0.5 mg/kg, 1 h) were observed under various pH values (2.5, 4.5, and 6.5) in both MnP (50 U/g) and LiP (50 U/g) groups, while DON degradability at 1 mg/kg was 85.5% after 50 U/g of LiP treatment for 7 h in simulated pig gastrointestinal tracts. Similarly, DON degradability at 5 mg/kg was 67.1% after LiP treatment for 4.5 h in simulated poultry gastrointestinal tracts. The present study demonstrated that SMS-extracted peroxidases, particularly LiP, could effectively degrade DON and inhibit the mycelium growth of F. graminearum KR1.